БОЛАЛАР ИЧКИ ОЛАМИ ТАЛҚИНИДА ФОЛЬКЛОРНИНГ ЎРНИ (А.Обиджоннинг “Кезаргон Бойчечак” қиссаси мисолида) (Scientific journal of the Fergana State University, 2023)
The article examines on example of the tale “Kezargon Boychechak” by Anvar Obidjon the formation of the ideas of national self-consciousness, the feeling of love for the Motherland. It features the writer’s ability to use the traditions of folklore.